The Moosonee hymnal [electronic resource] : translated into the Ojibbeway language - Horden, John, 1828-1893. (London : Society for Promoting Christian Language, 1891)
Text entirely in the Ojibwa language, in syllabic characters. Electronic reproduction. Mode of access: Internet. 44